(untitled) (Brazilian Journal of Radiation Sciences, 2019)
The edible flowers are increasingly used in culinary preparations, which require new approaches to improve their conservation and safety. Irradiation treatment is safe and an effective alternative for food conservation. Indeed, it can also guarantee food quality, increasing shelf-life and disinfestation of it. This technology gives us a versatile way to get good quality food, reducing post-harvest losses. Dianthus chinensis flowers, popularly known as Chinese pink, are widely used in culinary preparations, being also acknowledged for their bioactive components and antioxidant properties. The purpose of this study was to evaluate the antioxidant activity of D. chinensis flowers submitted to electron beam and gamma irradiation at 0, 0.5, 0.8 and 1 kGy. The antioxidant properties were evaluated through 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity, reducing power and β-carotene bleaching inhibition assays. Total phenolics were also determined by the Folin-Ciocalteu assay. The antioxidant activity was higher for irradiated samples, especially those treated with 0.8 and 1 kGy, independently of the radiation source, which showed the highest capacity to inhibit β-carotene bleaching. Accordingly, the applied irradiation treatments seemed to represent feasible technology to preserve the quality of edible flower petals, being able to improve the antioxidant activity